Assessment of an Objective Method of Dyskinesia Measurement in Parkinson's Disease. Issue 2 (2nd March 2018) - Chung, Kathryn A.; Lobb, Brenna M.; Murchison, Charles F.; Mancini, Martina; Hogarth, Penelope; Nutt, John G.
Abstract: Background: The goal of this study was to validate an objective method of measuring levodopa induced dyskinesia in Parkinson's disease (PD). Methods: To characterize agreement between the clinician‐based measure and a force plate, we assessed dyskinesia in PD subjects participating in a randomized and blinded clinical trial of an adenosine A2A anatagonist. Convergent validity and intra‐class correlations were evaluated between the objective force plate measure and clinician assessments. Results: All measures correlated across time and detected differences in treatments. Conclusion: Our results indicate that objective measure from a force plate is in scale agreement with clinical ratings of dyskinesia severity, indicating it as a reliable method to measure LID objectively but with greater resolution to detect changes in LID.